Antimicrobial growth promoters approved in food-producing animals in South Africa induce shiga toxin-converting bacteriophages from Escherichia coli O157:H7 - (:unkn) unknown (My University, 2023)
In this study, four antimicrobial growth promoters, including virginiamycin, josamycin, flavophospholipol, poly 2-propenal 2-propenoic acid and ultraviolet light, were tested for their capacity to induce stx-bacteriophages in 47 Shiga toxin-producing E. coli O157:H7 isolates. Induced bacteriophages were characterized for shiga toxin subtypes and structural genes by PCR, DNA restriction fragment length polymorphisms (RFLP) and morphological features by electron microscopy. Bacteriophages were induced from 72.3% (34/47) of the STEC O157:H7 isolates tested. Bacteriophage induction rates per induction method were as follows: ultraviolet light, 53.2% (25/47); poly 2-propenal 2-propenoic acid, 42.6% (20/47); virginiamycin, 34.0% (16/47); josamycin, 34.0% (16/47); and flavophospholipol, 29.8% (14/47). A total of 98 bacteriophages were isolated, but only 59 were digestible by NdeI, revealing 40 RFLP profiles which could be subdivided in 12 phylogenetic subgroups. Among the 98 bacteriophages, stx2a, stx2c and stx2d were present in 85.7%, 94.9% and 36.7% of bacteriophages, respectively. The Q, P, CIII, N1, N2 and IS1203 genes were found in 96.9%, 82.7%, 69.4%, 40.8%, 60.2% and 73.5% of the samples, respectively. Electron microscopy revealed four main representative morphologies which included three bacteriophages which all had long tails but different head morphologies: long hexagonal head, oval/oblong head and oval/circular head, and one bacteriophage with an icosahedral/hexagonal head with a short thick contractile tail. This study demonstrated that virginiamycin, josamycin, flavophospholipol and poly 2-propenal 2-propenoic acid induce genetically and morphologically diverse free stx-converting bacteriophages from STEC O157:H7. The possibility that these antimicrobial growth promoters may induce bacteriophages in vivo in animals and human hosts is a public health concern. Policies aimed at minimizing or banning the use of antimicrobial growth promoters should
Keywords: African Research